Development of service desk function through insourcing - Taskinen, Teresa (My University, 2016)
Nowadays, the majority of tasks and interactions of daily life and work are dependent on information technology (IT). Thus, any type of malfunction in IT hampers smooth work and can lead to significant problems. To cope with risky situations, the IT service desk function supports the daily operations of businesses, keeping them running smoothly. The service desk is a fundamentally valuable function for businesses and users because it serves to maintain users’ work efficiency by solving their IT-related problems. Moreover, companies need to thoroughly consider how they best obtain the service desk function. Insourcing is a business practice where a company takes back in-house previously outsourced operations. This is a worthy alternative because, as time passes, companies, as well as their needs, change. However, surprisingly few studies focus on insourcing arrangements. The aim of this thesis is to increase understanding about the development of the service desk function through insourcing by studying both theoretical and practical insights about the whole service desk insourcing process. The research questions are: what are the general requirements for the development of the service desk function through insourcing? How have the objectives of the service desk insourcing project been realized in the case company? This thesis consists of two main parts: a literature review and a single-case study. The theoretical part compiles essentials of service desk insourcing, including two main subjects: the service desk function and execution of insourcing. The empirical part examines and evaluates the service desk insourcing project at the case company. This company insourced its service desk in the summer of 2015 from an external service provider in the Nordic countries. The development project has been carried out quite recently, and this enables intriguing observations to be made of the whole service desk insourcing process and the people who participated in it. The empirical part has been conducted through a text analysis of the project and a questionnaire targeting the service desk employees. The findings underline that the service desk insourcing process includes a starting point, a service desk insourcing decision, the implementation of the decision, an evaluation of the results, and plans for the future. The main conclusion drawn from this research is that the service desk insourcing proved to be a successful move at the case company. This thesis further accentuates that service desk insourcing can offer notable benefits for companies, and offers a viable alternative for organizing and developing the service desk function to meet the changing needs of business.